Four novel species of Pleurotheciaceae collected from freshwater habitats in Jiangxi Province, China - He, Wen-Ming; Zhang, Jun-Bo; Zhai, Zhi-Jun; Tennakoon, Danushka Sandaruwan; Cui, Chao-Yu; Zhou, Jian-Ping; Chen, Ming-Hui; Hu, Hai-Jing; Yin, Hua; Gao, Yang; Hu, Dian-Ming; Song, Hai-Yan (Frontiers in Microbiology, 2024)
During an investigation of fungal diversity from freshwater environments in different regions in Jiangxi Province, China, four interesting species were collected. Morphology coupled with combined gene analysis of an ITS, LSU, SSU, and rpb2 DNA sequence data showed that they belong to the family Pleurotheciaceae. Four new species, Pleurotheciella ganzhouensis, Pla. irregularis, Pla. verrucosa and Pleurothecium jiangxiense are herein described. Pla. ganzhouensis is characterized by its capsule-shaped conidia and short conidiophores, while Pla. irregularis has amorphous conidiophores and 3-septate conidia. Pla. verrucosa has cylindrical or verrucolose conidiogenous cells, 1-septate, narrowly fusiform, meniscus or subclavate conidia. P. jiangxiense characterized in having conidiogenous cells with dense cylindrical denticles and short conidiophores. P. obovoideum was transferred to Neomonodictys based on phylogenetic evidence. All species are compared with other similar species and comprehensive descriptions, micrographs, and phylogenetic data are provided.